Pemikiran Abu al-Fadl al-Sinory Tentang Ritual Sembangyang dalam Kitab Ayatul Ahkam min Tafsir al-Qur’an - Najma, Dzatan; Abdul Hafidz , Mochammad (Javano Islamicus, 2024)
Tafsir Nusantara is considered to be quite helpful for the Indonesian people to understand the content of the Qur'an. In Seno-ri Tuban there is a scholar named K.H. Abu al-Fadl bin Abd Al-Shakur Al-Sinory who has the work of Tafsir Ayat al-Ahkam min a- quran al-Karim. The works produced are very important to be studied as an addition to the treasury of Nusantara tafsir science. This study uses descriptive-analytical method to examine the scientific background, the method of interpretation and how the interpretation is related to the verses of prayer. The conclusion of this study is that his tafsir consists of two major themes, namely the theme of fiqh worship and muamalah by using maudhu'i and ijmali methods. As for the theme of prayer, he emphasizes that prayer is something important that is mentioned in the sighat amar